1963
DOI: 10.1099/00221287-30-3-469
|View full text |Cite
|
Sign up to set email alerts
|

Cell-wall Constituents of Rickettsiae and Psittacosis-Lymphogranuloma Organisms

Abstract: SUMMARYThe taxonomic position of organisms belonging to the rickettsiae and psittacosis-lymphogranuloma groups is controversial. Although, like viruses, all pathogenic forms of these organisms are obligate intracellular parasites, in other respects they resemble bacteria. Since a cell wall, deriving its rigidity from mucopeptide, which contains the amino sugar muramic acid as a key constituent, has so far only been found in bacteria and the closely related blue-green algae, the presence of muramic acid in an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

1964
1964
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 48 publications
2
20
0
2
Order By: Relevance
“…While the lysozyme failed to inactivate a majority of the infective chlamydial particles, it consistently produced a significant reduction in chlamydial infectivity. This supports other chemical evidence that the cell walls of infective chlamydial particles do contain glycopeptide (3,4,9) and therefore are, in fact, structurally very closely related to the cell walls of bacteria. The limited degree of inactivation, however, suggests that lysozyme alone will not suffice to prevent ocular chlamydial infection, and if lysozyme is implicated at all in a "protective defense mechanism" against chlamydiae, it must operate in conjunction with other tear constituents (10).…”
Section: Results and Conclusionsupporting
confidence: 81%
“…While the lysozyme failed to inactivate a majority of the infective chlamydial particles, it consistently produced a significant reduction in chlamydial infectivity. This supports other chemical evidence that the cell walls of infective chlamydial particles do contain glycopeptide (3,4,9) and therefore are, in fact, structurally very closely related to the cell walls of bacteria. The limited degree of inactivation, however, suggests that lysozyme alone will not suffice to prevent ocular chlamydial infection, and if lysozyme is implicated at all in a "protective defense mechanism" against chlamydiae, it must operate in conjunction with other tear constituents (10).…”
Section: Results and Conclusionsupporting
confidence: 81%
“…Although Perkins & Allison (1963) detected muramic acid in several strains of Chlamydia, Manire & Tamura ( I 967) found none in meningopneumonitis elementary bodies or walls. There are three possible explanations for this discrepancy:…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…This fits to the notion that PG-loss renders FtsZ dispensable, like in mycoplasmas 6 or L-form bacilli 7 . While from genome sequences it is clear that chlamydiae do not possess FtsZ, the presence or absence of chlamydial PG has been highly controversial 8, 9, 10, 11, 12, 13, 14, 15, 16 . One early study reported the colorimetric detection of muramic acid in chlamydiae 14 , but more reliable chromatographic methods subsequently failed to confirm this result 11, 15 .…”
Section: Introductionmentioning
confidence: 99%
“…While from genome sequences it is clear that chlamydiae do not possess FtsZ, the presence or absence of chlamydial PG has been highly controversial 8, 9, 10, 11, 12, 13, 14, 15, 16 . One early study reported the colorimetric detection of muramic acid in chlamydiae 14 , but more reliable chromatographic methods subsequently failed to confirm this result 11, 15 . All attempts to purify chlamydial sacculi have failed 10, 12 and no periplasmic density layers have been detected between the inner and outer membranes of chlamydiae by electron microscopy (including for instance 17, 18, 19 ).…”
Section: Introductionmentioning
confidence: 99%